EFFECT OF GAMMA-RAY ON THE STABILITY OF STORED RBCs MEMBRANE - Muhsen, Thaer L (Al-Nahrain Journal of Science, 2009)
Blood bank stored RBCs were reported to undergo several changes including RBCs membrane protein changes. The present study was designed to investigate the responses of stored RBCs in term of membrane stability of cells to -ray. Stored RBCs for 15 days and 30 days was associated with a significant decrease in the stability of RBCs relative to (fresh RBCs). In addition, 1Gy gamma radiation did not change the stability of fresh or stored RBC. In contrast, 10Gy gamma radiation was associated with a further significant decrease in the stability of 15 days stored RBCs relative to (fresh RBCs). However, an apparent significant increase in the stability was observed for the RBCs stored for 30 days and irradiated by 10Gy gamma radiation.